STUDI OPERASIONAL PENINGKATAN PEMAKAIAN KONTRASEPSI IUD DI PROVINSI BALI - Nilakusmawati, Desak Putu Eka; Nitiyasa, Gde (PIRAMIDA; Vol 8, No. 2 Desember 2012, 2012)
The purpose of this study is to determine: (1) The difference in the characteristics of respondents who use IUD (Intra Uterine Device) contraception with respondents who used the non-IUD kotrasepsi, (2) The reasons respondents chose to use IUD contraception, and (3) The reasons respondents did not choose to use IUD contraception. Locations in this study includes all regency/cities in the province of Bali. Sources of data in this study using primary data sources were collected through questionnaires and secondary data sources. Sampling studies using multistage sampling technique for selection of districts in each regency/city and selection of villages in each district. Sample unit in this study is elligble couples, which one of them when the study was using one of modern contraceptives. Samples were taken using nonprobability sampling approach, using accidental sampling. The sample size was set at 3000 elligble couples, with details 994 elligble couples are using IUD contraception and 2006 elligble couples using non-IUD contraception. The data collection technique using a structured interview technique, documentation, and observation. Data analysis techniques using descriptive analysis. The results showed that the differences in the characteristics of IUD responders and non-IUD are: (1) From the aspect of age found that IUDs are relatively older respondents than non-respondents IUD, (2) Respondents IUD more highly educated respondents than non-IUD, (3) IUD responders has children ever born relatively more than non-IUD respondents, (4) average of children still alive for respondents IUD was 2.20 children, while for non IUD respondents average is 2.09, and (5) IUD responders more likely to have age of the youngest child at the age higher than non-IUD responders. The reasons respondents chose to use IUD contraception, IUDs can be effective is that after installation, duration of IUD use is relatively long, and very effective. While the reasons respondents did not choose to use IUD contraception, is due menstrual longer and much, and more pain during menstruation.
Keywords: contraception; IUD; Intra Uterine Device; elligbe couples